(untitled) (Bioscience Journal, 2018)
The present study was conducted to determine the quality and composition of colostrum samples obtained from Simmental and Brown Swiss heifers on a Turkish dairy farm in Ã–demiÅŸ, Ä°zmir. The average volume of colostrum obtained from Simmental and Brown Swiss heifers at the first milking was 3.4 L and 3.8 L, respectively. Average colostrometer (Ig) and Brix values were determined as 105.1 mg/mL and 104.9 mg/mL, 29.97 % and 29.68 % of the samples (P>0.05). No significant differences were observed between colostrums’ chemical compositionsâ€”including total solids, total protein, solids-not-fat, somatic cell counts (SCC), total bacterial counts (TBC), and energy values of the breeds - except for lactose concentration (P<0.05). The means of TBC were 781,000 and 634,000 CFU/mL for Simmental and Brown Swiss, respectively. The correlations between colostrometer and Brix values in Simmentals and Browns Swiss were 0.85 and 0.81, respectively (P<0.01). On the other hand, the correlations between Log10SCC and Log10TBC in both breeds were found to be 0.66 and 0.65 (P<0.05), respectively. According to the results of the present study, the fat, protein, lactose, and total solid concentrations of both Simmental and Brown Swiss (dual-purpose breeds) were higher than the values reported for Holstein dairy breeds. Although colostrum quality of both breeds was found to be good in terms of Ig concentration, their total bacterial counts were high. Bacterial counts can be reduced with adequate hygiene practices and good colostrum management.